The Effects of Hedge Fund Interventions on Strategic Firm Behavior - Khurana, Inder K.; Li, Yinghua; Wang, Wei (Management Science, 2018)
We examine the impact of hedge fund interventions on target firms’ strategic behavior, specifically their voluntary disclosure and earnings management strategies. We find a decrease in both the likelihood and the frequency of management earnings forecasts conveying bad news and an increase in the level of real earnings management following interventions by hedge fund activists. Additional evidence suggests that managers substitute between voluntary disclosure and earnings management strategies in resisting hedge fund attacks. We also find that withholding of bad news is more pronounced when hedge fund activists pose greater threats to the target firm’s management and when the intervention lasts for a relatively short time period. Our results are consistent with firms behaving strategically in response to heightened career/reputation concerns and endangered corporate control arising from hedge fund activism. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2816 . This paper was accepted by Suraj Srinivasan, accounting.